(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the clinical symptoms, changes in peripheral blood count, neutrophil to lymphocyte ratio (NLR) and CRP during asthma exacerbation in children, and investigate the association between NLR and some features and severity of asthma exacerbations, as well as the correlation between NLR and inflammatory markers. Subject and method: A descriptive cross-sectional study of 156 pediatric patients hospitalized for asthma exacerbation at the Department of Pediatric Respiratory, Immunology, and Allergy, Pediatrics Centre - Hue Central Hospital and the Department of General Pediatrics - Hospital of Hue University of Medicine and Pharmacy from October 2022 to March 2023. Results: The age group 2 - 5 years old accounted for the biggest percentage (69.9%), with a male/female ratio of 2/1. Common symptoms of asthma exacerbation included wheeze (93.6%), increased respiratory rate (88.5%), and utilizing abdominal muscles when exhaling (76.9%), although diffuse hypoventilation and wheezing occurred at a low rate (28.2% and 24.3%, respectively). 22.4% of children were hospitalized for acute asthma exacerbation. The mean number of white blood cells in asthma exacerbation was 13.0 ± 4.4 (x109/L); and this number was higher in children with severe asthma exacerbation than in children with moderate and mild asthma exacerbation (13.9 ± 4.2 vs 12.9 ± 4.5 and 9.1 ± 2.0; p; < 0.05). For each peripheral blood cell in particular, the mean number of neutrophil was higher in children with severe asthma exacerbation than in children with moderate and mild asthma exacerbation (8.9 ± 38 vs 7.1 ± 3.2 and 4.0 ± 1.7; p < 0.05). Similarly, there was significantly difference in mild and moderate asthma exacerbation with severe asthma exacerbation based on eosinophils count (median 450.0 vs 230.0 and 234.0; p < 0.05); however the number of lymphocytes did not differ according to the severity of asthma exacerbation (p > 0.05). Children with asthma exacerbation had an average NLR of 2.1 ± 1.4 and this ratio was significantly higher in children with severe asthma exacerbation compared with children with moderate and mild asthma exacerbation (2.9 ± 1.6 compared with 1.9 ± 1.2 and 1.1 ± 0.7; p < 0.05). An NLR cutoff value >2.17 demonstrated good discriminatory ability for identifying severe asthma exacerbations (AUC 0.79; 95% CI: 0.68-0.91; p < 0.001). However, there was no correlation between NLR and the clinical features of systemic inflammation nor with other inflammatory markers in asthma exacerbation. Conclusion: The number of neutrophils, eosinophils and neutrophil to lymphocyte ratio are higher in severe asthma exacerbation. These markers should be given greater clinical attention when approaching asthma exacerbation in children.